Treatment of Partially Stabilized Landfill Leachate using Combined Ammonia Stripping and GAC Adsorption - Lennevey, Kinidi (UNIMAS, 2022)
Partially stabilized leachate is known to contain contaminants harmful to the environment. The combined physicochemical treatment was generally used to treat these recalcitrant However, the existing technology is still unsatisfactory to fulfil strict discharge limits and is subjected to various operational issues. This thesis aims to evaluate the effectiveness of combining ammonia stripping and subsequent acidification as a pre-treatment for GAC adsorption and also evaluate the impact of ammonia removal efficiency on the economic cost of the full-scale ammonia stripping system. The partially stabilized leachate was characterized by a high COD (2800 mg/L), UV254 (15.92), and ammonia (920 mg/L) concentration. A response surface methodology (central composite design) was used to optimize the variables such as pH (9-12), air to water ratio (5-10L/Air/min/L-Leachate), and temperature (30-60 oC) for the lab-scale diffused ammonia stripper. Then, the effect of lime (from the ammonia stripping process) and acidification for optimization GAC adsorption was evaluated by varying the lime dosage (0 to 20 g/L) and pH (2 to 12), respectively. Next, the equilibrium isotherms and kinetics of the adsorption process were investigated. Finally, the economic feasibility of the proposed treatment was conducted using Aspenplus®. The optimization process using RSM for the diffused ammonia stripper had predicted the optimum condition for ammonia removal, corresponding to 95.6% ammonia removal. The acidification after lime treatment has significantly improved the adsorption of organics (COD) by more than 90%, showing a significant improvement in the adsorption performance by using the granular activated carbon. The equilibrium and kinetic adsorption follow the Redlich-Peterson isotherms (R2: 0.99902) and pseudo-second-order degree kinetics (R2: 0.993-0.998) The economic optimums for the ammonia stripping and absorption process scale-up simulation were found to be at RM338.66/kg (79.60 US$/kg) of ammonia removed at ammonia concentration of 244 ppm with 95% removal efficiency at an operating temperature of 60 oC. In conclusion, these results demonstrate that the combined process is an effective treatment for the treatment of partially stabilized leachate in complying with strict discharge limits.